Synthesis, Characterization and Electrical Properties of ZnO Nanoparticles Dispersed in Poly(vinyl acetal)/PVA Composite - A. Latif, Issam; M. Abdullah, Hilal; H. Marza, Sundus; H. Al-Dujaili, Ammar; T. Bakir, Emad (Asian Journal of Chemistry, 2013)
Poly 4-methyl benzylidene vinyl alcohol [poly(vinyl acetal)] was prepared and characterized with IR spectroscopy and the melting point measured, ZnO nanoparticles were prepared and with AFM and XRD characterized, studied and the nanoparticles size measured. Poly (vinyl acetal)/PVA composite were prepared by ultrasonically mixing with different ZnO nanoparticles per cent. Each mixture was fabricated in film and casted in 5 cm × 5 cm glass caste. The real and imaginary dielectric permittivity and electric modulus were for the prepared films studied.